If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-3=7x-2
We simplify the equation to the form, which is simple to understand
5x-3=7x-2
We move all terms containing x to the left and all other terms to the right.
+5x-7x=-2+3
We simplify left and right side of the equation.
-2x=+1
We divide both sides of the equation by -2 to get x.
x=-0.5
| 3z-21=-57+9z | | 5y+25=3x | | 6(5d-8)= | | 7(h+3)=6(-3) | | m+9=-3m+11 | | 3x+1=x+10 | | 6(x+1)-4=3x+2 | | x^4y-81y=0 | | -54=6+6x | | 6+4x-6=4+(3)x-6 | | 4x-14=22 | | 7x+y+5z=-8 | | 7x^2+30=-41x | | 8(b-4)= | | 7a^2-38a=-15 | | 5x^2=-21-38x | | x(2x+2p)-p=-4 | | 7b^2=-43b-40 | | p^2=8p-16 | | 3v^2+15=14v | | 4x+2z=42 | | n^2-4n=32 | | 5k^2-35k=-60 | | 42-x=26 | | 4x+2=5-7x | | 2b^2+128=32b | | 6x^2-48=12x | | 4v^2+16v=0 | | 12x-12=36+8x | | 5n^2+20=25n | | 8x^2+64x=0 | | 8x+2+7x-10=22 |